Impact of Gaslighting on Depression, Stress and Anxiety Among Married Individuals in Pakistan - Nayab, Rehmat; Asad Nauman; Mahnoor Khalid; Nashila Mukhtar, (Dialogue Social Science Review (DSSR), 2025)
Gaslighting is a Psychological manipulation and form of emotional abuse, that seeks to make an individual doubt their perception and reality. It is subtle, damaging, and can have serious effects on mental health such as Depression, Stress, and Anxiety. However, the problem is being studied in Western culture in different setting, but little is known about its effects on mental health in the Pakistani culture, particularly among married individuals. The purpose of the study is to examine the relationship between Gaslighting, Depression, Stress, and Anxiety among married individuals in Pakistan. Additionally, It also explores the gender differences in whether men or women who experiencing more gaslighting. A random sampling method was used to choose 200 married individuals consisting 74 males and 126 females. Data were gathered through questionnaires which include the Gaslighting scale and DASS21 scale. Statistical analysis including correlation and mean comparisons were used to see the relationship between variables and gender differences. The results revealed a significant correlation between the variables Gaslighting, Depression, Stress, and Anxiety. Additionally, in terms of gender differences, the results shows women experiencing it much more frequently than males did. Finally, the study emphasizes how critical it is to acknowledge gaslighting as a severe type of emotional abuse that disproportionately targets women. To address, gaslighting and its effect on mental health and to promote well-being and good relationships for couples in Pakistan, culturally tailored treatments are required.